Usos colectivos, mancomunales y ganadería a través del Becerro Galicano de San Millán de la Cogolla - Esther Pascua Echegaray (Mélanges de la Casa de Velázquez)
Starting from the documentation and the making of the Becerro Galicano de San Millán de la Cogolla, the article identifies the spaces of collective management by the rural communities of the Castilian-Navarre border and the shared use of communal land between various villages during the 10th and 11th centuries. The use of monasteries and churches as a gateway to participation in the governance of the villages did not prevent the monastery from having to negotiate its presence in the communities, while at the same time acting in favor of the formalization of communal spaces and homogenization of cattle practices and of wood exploitation.